Hepatoprotector effect of Sesbania grandiflora L flowerâs extract to Liver Cell Structure Damage of Mice caused by Over Reheated Palm Oil - Fastiati, Rizka Abida; Listyaningsih, Endang; Mashuri, Yusuf (Nexus Biomedika, 2015)
Background:Sesbania grandiflora L flower has high antioxidant activity.Â  This activity is caused by phytochemical ingredients of Sesbania grandiflora L flower, such as vitamin C, flavonoidsÂ  and tannin. The aims of this research were to know the hepatoprotector effect of Sesbania grandiflora L flowerâs extract to the liver cell structureÂ  damage ofÂ  mice caused by over reheated palm oil and to find out dose escalation ofÂ  Sesbania grandiflora L flowerâs extract that can enhance the effect. Methods:This research was laboratory experimental study with the post-test only controlled group design. The tested animal used in this experiment were male mice, Swiss webster strain.The research population were 30 male mice divided into 5 groups, each group consisted ofÂ  6 mice. TheÂ  negative control group (KKn) was given distilled water, while the positive control group (KKp) was given over reheated palm oil. The 1st treatment group (KP1), the 2nd treatment group (KP2) and the 3rd treatment group (KP3), all, were given Over Reheated Palm Oil as much asÂ  0.06 ml/ 20 gr BW andSesbania grandiflora L flowerâs extract with dose 7 mg, 14 mg and 28 mg per 20 gr BW of mice, consecutively. The liver histological images were assessed by the sum of the cell nuclear pyknosis, karyorrhexis, and karyolysis. Data were analyzed by using One-Way ANOVA test and Post Hoc Test (LSD) (Î±=0.05). Results:One-Way ANOVA test showed that p value was 0.000 (p < 0.05).The results of the post hoc multiple comparisons test showed the significant differences between group KKn-KKp, KKn-KP1, KKn-KP2, KKn-KP3, KKp-KP1, KKp-KP2, KKp-KP3, KP1-KP2, KP1-KP3, and KP2-KP3 Conclusions:Sesbania grandiflora L flowerâs extractÂ  has a protective effect on liver cell structure damage of mice (Mus musculus) caused by over reheated palm oil and the escalated dose of Sesbania grandiflora L flowerâs extractÂ  can enhance the effect. Keywords:Histological structure of liver damage, over reheated palm oil, Sesbania grandiflora L.